The Excellence Of ITDC Nusa Dua Bali As A World-Leading Mice Tourism Venue - Prianta, Putu Agung; Sulistyawati, Anastasia (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
MICE is a promising tourism industry sector in Indonesia, driven by global business growth and the need for companies to hold meetings, incentives, and business trips. This study aims to understand: the history of the establishment of ITDC Nusa Dua, Bali, as the most comprehensive integrated tourism area in Indonesia; to understand the advantages of ITDC, as a leading MICE tourism venue in the world; and to understand the benefits of MICE tourism in Nusa Dua, Bali, for the development of various sectors in Bali and Indonesia. The theories used are MICE theory and sustainable tourism theory. Qualitative research method. The data collection technique is literature study. The results of the study show that the development of convention tourism has long been designed by the Indonesian Government together with UNDP since 1969, culminating in the establishment of BTDC in 1973. The Nusa Dua Tourism Area, which is now ITDC, became the first integrated MICE destination with international standards. Its success is supported by strategic factors such as geographical location, natural beauty, accessibility, and thorough planning by international consultants. MICE tourism contributes significantly to the growth of various sectors in Bali, both directly in organizing events and other supporting sectors.